Nuclear coherent population transfer to the Th 229m isomer using X-ray pulses - Kirschbaum, Tobias; Minkov, Nikolay; Pálffy, Adriana (Physical Review C - Nuclear Physics, 2022)
Population of the 8 eV Th229m isomer via the second nuclear excited state at 29.19 keV by means of coherent X-ray pulses is investigated theoretically. We focus on two nuclear coherent population transfer schemes using partially overlapping X-ray pulses known from quantum optics: Stimulated Raman adiabatic passage, and successive π pulses. Numerical results are presented for three possible experimental setups. Our results identify the Gamma Factory as the most promising scenario, where two ultraviolet pulses combined with relativistically accelerated ions deliver the required intensities for efficient isomer population. Our simulations require knowledge of the in-band and cross-band nuclear transition probabilities. We give theoretically predicted values for the latter and discuss them in the context of recent experiments.
CRIS-Team Scopus Importer:2022-07-22